Effects of sintering on mechanical properties of biologically derived hydroxyapatite - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2002)
In this study, the change in the mechanical properties of hydroxyapatite (HA), which is the main mineral content of bone and teeth; commonly used as an implant material, for different sintering temperatures is tested. Although HA shows great biocompatibility with the human body, its applications are limited to non load-bearing areas and coatings due to its low mechanical properties, These mechanical properties can be improved substantially by sintering. In this study, naturally produced HA from human teeth is sintered, density, microhardness measurements and compression tests are performed in order to find the optimum sintering temperature; and the results are compared with the synthetically derived HA properties from the literature.
Keywords: hydroxyapatite; sintering; PHOSPHATE; CERAMICS; STRENGTH; BONE